PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK AQUA (STUDI KASUS PADA MAHASISWA STIENAS BANJARMASIN ANGKATAN 2015) - Rizki Amalia Afriana; Penta Lestarini Budiati; Eko Prabowo (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,The purpose of this research is to find out whether the marketing mixconsisting of product (X1), price (X2), promotion (X3) and location (X4)have partial and simultaneous effect on purchasing decision of drinkingwater in Aqua packaging, and to know from the four marketing mix variablesare the most dominant influence on the purchase decision of drinking waterin the packaging of Aqua brand.The population of this study are 200 people , they are all students ofSTIENAS Banjarmasin Class of 2015. Methods of data analysis in this studywere conducted descriptively quantitatively with multiple linear regressionusing the help of SPSS program version 16.0.The result of the research shows that marketing mix consisting ofpromotion variable (X3) and location (X4) have partially significant effect onpurchasing decision of drinking water in Aqua brand packaging, whileproduct (X1) and price (X2) variable have no significant effect partiallypurchase decision of drinking water in Aqua brand packaging